URGENSI RASM UTSMANI; (Potret Sejarah dan Hukum Penulisan Al-Qur’an dengan Rasm ‘Utsmani) - Zaenal Arifin Madzkur (Khatulistiwa, 2011)
The majority of Muslims agree that the Rasm of Utsmani played a significant role in the history of the writing styles of Al Qur‟an. Since 1923 (1924 H) after the standardization of the writings styles of the Al Qur‟an in Egypt, there has not been found any other writing styles of the Al Qur‟an that are “incorrect” according to the standard style by Khalifah Utsman. This fact has inspired the emergence of a new brand of discipline in the field, namely “the study of Knowledge of Rasm of Utsmany” which includes the knowledge and main requirements of writing the Al Qur‟an in Rasm of Utsmani. This article attempts to explore the view points of Muslim scholars in the history of the writing process of the Al-Qur‟an and the status of writing the Alqur‟an using the Rasm of Utsmani.